2017
DOI: 10.1680/jtran.15.00110
|View full text |Cite
|
Sign up to set email alerts
|

Lane-based car-following behaviour based on inductive loops

Abstract: It is assumed that car-following behaviour is the same in different lanes of traffic flow, but it is necessary to investigate whether car-following behaviour in all lanes, in congested and non-congested conditions, is the same or not. For this purpose, the traffic data for a freeway in Iran (the Tehran–Qom freeway) were investigated. The results showed that by choosing the lane closer to the median, driving cautiousness will be reduced. This finding can not only be attributed to increasing speed, which is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It could be said that in this case, free driving occurs. According to a previous study by the authors [23] and also, according to the headway and lateral distance diagrams in this paper, it can be found that most drivers began to adopt a lateral distance in distance less than 2 sec. Hence, most probably, this value can be called as the threshold for the following behavior.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It could be said that in this case, free driving occurs. According to a previous study by the authors [23] and also, according to the headway and lateral distance diagrams in this paper, it can be found that most drivers began to adopt a lateral distance in distance less than 2 sec. Hence, most probably, this value can be called as the threshold for the following behavior.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of rear-end collision in Iranian roads indicates the fact that Iranian drivers often do not adhere to appropriate and recommended headway, and use less than 2 seconds for car-following. On the other hand, in a study conducted by Khansari et al in 2016 in Iran, they showed that about 85% and 70% of Iranian drivers accept time headway less than 3 seconds in congested and uncongested conditions [23]. At least the data included 3 sec time headway for all speeds, as shown in Table 1, which makes sure almost all following cars were recordable.…”
Section: Figure 1 Area Covered By the Traffic Camera And Location Ofmentioning
confidence: 88%
“…us, investigating CF can help to prevent and predict rear-end collision and also can enhance traffic safety. Several researches have confirmed that both the CF model and its estimated parameters can vary for different drivers and situations [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…Khansari et al investigated the car-following behavior in different lanes of a freeway in Iran. e results showed that closer lanes to the median have higher speed and lower headway, and the capacity difference between inner and outer lanes is from about 7% up to 24% [12]. An analysis of real data on a three-lane freeway was carried out by Duret et al and showed that the fraction of the total flow in the median lane increases linearly, whereas the opposite trend is observed for the center lane and particularly for the shoulder lane [13].…”
Section: Introductionmentioning
confidence: 99%